1976
DOI: 10.1115/1.3450450
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Gas Radiation in a Laminar or Turbulent Pipe Flow

Abstract: The temperature profile and the radiative and convective wall-heat fluxes for a hydro-dynamically established flow of a nongray gas in a cylinder are calculated numerically for laminar or turbulent flow. Turbulent eddy viscosity is represented by a two-region model having a near-wall-region and a far-from-wall region. Gas properties are represented by the exponential-winged band model. The controlling parameters are Nrm, the ratio of radiation conductance to molecular conductance, τR,i, the maximum spectral op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Similar findings, particularly regarding the existence of a fully developed temperature profile, have been reported in analyses by Liu and Thorsen [11] and by Pearce and Emery [12]. Recently Balakrishnan and Edwards [10] compared their results for radiation and total Nusselt numbers at large distances from entry to the results of Wassel and Edwards [9] for thermally and hydrodynamically established turbulent flow in a pipe. These authors found that maximum errors in these Nusselt numbers were 2.2 percent and 7 percent, respectively, corresponding to radiation-to-conduction ratio of 10.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similar findings, particularly regarding the existence of a fully developed temperature profile, have been reported in analyses by Liu and Thorsen [11] and by Pearce and Emery [12]. Recently Balakrishnan and Edwards [10] compared their results for radiation and total Nusselt numbers at large distances from entry to the results of Wassel and Edwards [9] for thermally and hydrodynamically established turbulent flow in a pipe. These authors found that maximum errors in these Nusselt numbers were 2.2 percent and 7 percent, respectively, corresponding to radiation-to-conduction ratio of 10.…”
Section: Introductionsupporting
confidence: 66%
“…Figure 1 shows the geometry and coordinate system used. The governing equations in nondimensional form can be given as [19] , , d6 d 2 9 1 dq R * u(n) -= d£ d? ; 2 …”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heat transfer by mixed convection and radiation has not been studied extensively. Forced convection in a channel with radiation has been under investigation by many researchers [16][17][18][19] for ducts with prescribed heat fluxes and temperature distributions on wall surface. These studies used various approximate methods for radiative transport in the medium.…”
Section: Introductionmentioning
confidence: 99%
“…The emission bands of CO 2 and water vapour are centred in the infra-red region [24], which will not be recorded by the camera. Therefore, their interference can be neglected.…”
Section: Interferences With Soot Luminositymentioning
confidence: 99%